ANALISIS OMSET DAN POSISI BERSAING PADA KLASTER USAHA KECIL MENENGAH (UKM) SEPATU KOTA MOJOKERTO - Fitanto, Bahtiar (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
This articles describes about turnover and competitiveness position of footwear smalland medium scale enterprises (sme’s) at Mojokerto, East Java Province. SME’s clus-ter approach is used to get the full maps of the ptroblem and policies that are needed.Development of small and medium scale enterprises is plays a crucial role for localeconomic development. This article is important because there are thousands of foot-wear small and medium scale enterprises in Mojokerto.Keywords: small and medium scale enterprises, local economic development, clus-ter